(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Department of Neurosurgery, Samarkand State Medical University. Pituitary tumors are a group of benign, malignant, and less often malignant tumors of the anterior (adenohypophysis) lobe of the gland. They make up about 15–25% of all neoplasms of the intracranial zone. This pathology equally often affects both men and women, whose average age is 30–40 years. Benign pituitary tumors (or adenomas) prevail over malignant pituitary pathology and allow complete surgical removal with minimal risk of disease recurrence [